Kontrol Nilai Terhadap Sains - Muhammad Zaini (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2017)
The advancement of human science can create various forms of technology. For example, creating an airplane and making bombs that initially aims to facilitate human work, but then these objects are used also for negative purposes which cause disaster for humans themselves. From this phenomenon then science must be put proportionally and side with the values of goodness and humanity in order to prevent disaster and catastrophe.